Leonardo and the Last supper - King, Ross, 1962- (New York : Walker & Company, 2012)
Tells the complete story of the creation of The Last Supper mural: the adversities suffered by the artist during its execution; the experimental techniques he employed; the models for Christ and the Apostles that he used; and the numerous personalities involved -- everyone from Leonardo's young assistants to Ludovico Sforza, the Duke of Milan who commissioned the work.
The Last Supper : with Apostles identified -- The Bronze Horse -- Portrait of the artist as a middle-aged man -- The Cenacolo -- Dinner in Jerusalem -- Leonardo's court -- The Holy League -- Secret recipes -- "Trouble from this side and that" -- Every painter paints himself -- A sense of perspective -- A sense of proportion -- The beloved disciple -- Food and drink -- The language of the hands -- "No one loves the Duke" -- Epilogue: Tell me if I ever did a thing.
Includes bibliographical references and index.
Keywords: Leonardo, -- da Vinci, -- 1452-1519.; Leonardo da Vinci, -- 1452-1519.